2013
DOI: 10.1016/j.apenergy.2012.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Economic and environmental impact of lead-acid batteries in grid-connected domestic PV systems

Abstract: 14

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(48 citation statements)
references
References 17 publications
(1 reference statement)
2
40
1
1
Order By: Relevance
“…Similar approaches have been used to estimate the impact of electric vehicles in Australian power systems, 38 bulk electricity storage in the Texas power system 39 and lead-acid batteries in Great Britain's power system. 40 All studies found that storage could have a negative environmental impact and emphasised a possible trade-off between operating storage for private benefits (i.e. maximising profit) rather than social benefits (i.e.…”
Section: Estimating Short-run Marginal Emissions Factorsmentioning
confidence: 99%
“…Similar approaches have been used to estimate the impact of electric vehicles in Australian power systems, 38 bulk electricity storage in the Texas power system 39 and lead-acid batteries in Great Britain's power system. 40 All studies found that storage could have a negative environmental impact and emphasised a possible trade-off between operating storage for private benefits (i.e. maximising profit) rather than social benefits (i.e.…”
Section: Estimating Short-run Marginal Emissions Factorsmentioning
confidence: 99%
“…Porém quando se analisa a fatura energética mensal em hipótese nenhuma, mesmo nos meses onde a geração será maior que o consumo, está será gratuita, tendo em vista a cobrança das taxas de consumo mínimo (por exemplo: iluminação pública) pelas concessionárias (MCKENNA et al, 2013).…”
Section: Sistemas Conectados a Rede Elétricaunclassified
“…The study of integrated PV-BESs on the United Kingdom FIT policy is addressed in [42]; McKenna et al state that the PV-BES combination in the UK is not a convenient operation as, even if there is a feed-in tariff, there is no case of financial convenience in adopting lead batteries. Such a conclusion is valid even if considering ideal batteries without leaks and with an optimistic life expectancy.…”
Section: The Case Of the United Kingdommentioning
confidence: 99%